ANAK ANGKAT DALAM PERSPEKTIF TAFSIR KEMENTERIAN AGAMA RI : KAJIAN AL-QUR’AN DAN TAFSIRNYA EDISI YANG DISEMPURNAKAN - Lulu Khairunnisa (Jurnal Studi Qur'an dan Tafsir, 2024)
In view of the law, the relationship of a child with his or her parent may be disconnected due to the adoption of a child; even an adopted child gets a special call from his or her adopted parent. Islamic law even recommends child adoption only in shifting obligation to provide everyday living, educate, nurture, and others in the context of worshiping Allah. However, the fact is that in the process of this adoption, acts of violence often occur toward an adopted child or vice versa. The writer uses library research in this study by making al-Quran and enhanced interpretation edition, using the qualitative method with a descriptive approach concerning the interpretation of adopted child cases in Indonesia, which is explained in the interpretation of the Ministry of Religion of Indonesia. From this study, then it is found that adopting a child does not bring any cause to the law in blood relationships, guardianship relationships, and inheritance relationships with the adopted parent. An adopted child receives a share of the inheritance of his or her adopted parent by way of a gift or written or spoken testament by his or her adopted father before his death. Therefore, it is advisable to adopt a child with a kinship relationship, to be far from mahrom problems.